2017
DOI: 10.3892/etm.2017.5084
|View full text |Cite
|
Sign up to set email alerts
|

Snail1 is positively correlated with atrial fibrosis in patients with atrial fibrillation and rheumatic heart disease

Abstract: The present study investigated the association between Snail1 and atrial fibrosis in patients with atrial fibrillation (AF) and rheumatic heart disease (RHD) and to determine the possible mechanism underlying this interrelation. A total of 19 patients were included in the current study and were divided into two groups: A sinus rhythm (SR) group (n=9) and an AF group (n=10). All patients underwent heart valve replacement surgery, during which ~200 mg right atrium tissue was obtained. Hematoxylin and eosin and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…42 Mechanistically, AF-dependent atrial fibrosis has been linked to elevated atrial expression levels of Snail1 that were found to be associated with increased expression of canonical Wnt 1, Wnt3A, and Wnt8A and the non-canonical family members Wnt5A and Wnt11. 43 Adenoviral overexpression of miR-27b-3p in rats reduced the duration and incidence of induced AF episodes and, notably, this was accompanied by reduced atrial fibrosis and fibrotic gene expression and diminished phospho-β-catenin and Wnt3A levels. 44 A similar decrease in profibrotic gene expression and fibrosis could be observed in primary rat fibroblasts upon over-expression of DACT2, which in HL-1 cells also reduced the phosphorylation of β-catenin.…”
Section: Wnt Signaling In Atrial Fibrillationmentioning
confidence: 96%
“…42 Mechanistically, AF-dependent atrial fibrosis has been linked to elevated atrial expression levels of Snail1 that were found to be associated with increased expression of canonical Wnt 1, Wnt3A, and Wnt8A and the non-canonical family members Wnt5A and Wnt11. 43 Adenoviral overexpression of miR-27b-3p in rats reduced the duration and incidence of induced AF episodes and, notably, this was accompanied by reduced atrial fibrosis and fibrotic gene expression and diminished phospho-β-catenin and Wnt3A levels. 44 A similar decrease in profibrotic gene expression and fibrosis could be observed in primary rat fibroblasts upon over-expression of DACT2, which in HL-1 cells also reduced the phosphorylation of β-catenin.…”
Section: Wnt Signaling In Atrial Fibrillationmentioning
confidence: 96%
“…The Wnt signalling pathway involves multiple signal molecule-mediated transduction pathways, and the activation of this pathway is observed in several cardiovascular pathologies ( 28 ). This study ( 27 ) extended the prevalence of the Wnt signalling pathway in cardiovascular disease to RHD and highlighted Snail1. The Wnt signalling pathway and Snail1 are implicated in the EMT process.…”
Section: Selection and Search Criteriamentioning
confidence: 79%
“…Wnt signalling pathway and RHD. Guo et al (27) found that the Wnt signalling pathway increased the expression of Snail1 and participated in the process of RHD-induced atrial fibrosis. The method they used was similar to the three studies on MAPK mentioned above, i.e., comparison of the SR and AF groups of patients with RHD.…”
Section: Signalling Pathways Implicated In the Pathogenesis Of Rheumamentioning
confidence: 99%
“…Secondly, the rs 2040862, nearest to the WNT8a gene, was associated with AF in our PRH cohort. WNT8a is part of the Wnt signaling pathway, and its expression is linked to increased collagen deposition and fibrosis around atrial cardiomyocytes, which is essential for providing a substrate for AF to develop [ 30 ]. Table 6 organizes each relevant SNP and the closest gene of association.…”
Section: Discussionmentioning
confidence: 99%